Berbakti Kepada Orang Tua dalam Ungkapan Hadis - Astuti, Hofifah (Jurnal Riset Agama, 2022)
The purpose of this study is to discuss the command to be filial to parents in the hadith. This research method uses a qualitative type through literature study by applying content analysis. The discussion of this research includes the meaning of birrul walidain (filial piety to parents), the hadith orders birrul walidain (filial piety to parents), the forms of birrul walidain, and the virtues of birrul walidain (filial piety to parents). This study concludes that birrul walidain or filial piety to both parents has a special position in Islamic teachings. The matter of filial piety to parents has been regulated both in the Qur'an and Hadith. Devotion to parents according to the hadith is an obligation equivalent to faith and jihad and taqwa which applies not only when parents are still alive but also when they have died. This research is expected to have benefits for enriching the treasures of Islamic knowledge.